Vers la fin de l’illusion développementale en ville ? Défiances silencieuses dans les sites de condominium d’Addis-Abeba (Éthiopie) - Marie Bridonneau (L'Espace Politique)
Since the mid-2000s, the condominiums have embodied the Ethiopian developmental state in the capital city. The condominium project is a massive program of collective housing construction and social access to ownership. There is a convergence between the segments of the urban population that these spaces concentrate, and those on which the Ethiopian government's political projects are focused: the intermediate social groups. We offer here a first assessment of a public policy that has deeply transformed the urban society. The condominium reveals the state's capacity to restructure the social space. This article provides an analysis of Ethiopian urban authoritarian situations through the observation of Addis Ababa condominium places, that are a special place for observing daily situations of silent resistance and circumvention, adaptations and consent to State’s domination.